Concepts of Fitness and Wellness - Flynn, Scott; Jellum, Lisa; Howard, Jonathan; Moser, Althea; Mathis, David; Collins, Christin; Henderson, Sharryse; Watjen, Connie (Open textbook library., 2018)
This open textbook for Concepts of Fitness and Wellness at Georgia Highlands College was created through a Round Seven ALG Textbook Transformation Grant.